Do Environmental Interventions Impact Elementary School Students' Lunchtime Milk Selection?. (20th February 2013) - Goto, Keiko; Waite, Alexandra; Wolff, Cindy; Chan, Kenny; Giovanni, Maria
Abstract: This paper examines whether environmental interventions increase elementary‐school students' selection of white milk in the school cafeteria. At intervention school one, white milk was easily accessible, but students had to ask for chocolate milk. Here, intervention students significantly increased their selection of white milk. Further, there was no significant change in the ratio of white milk consumed to white milk selected during the examined period. At intervention school two, the visual cue of a threefold greater quantity of white compared to chocolate milk did not significantly alter selection patterns. These findings demonstrate that school‐based practices that apply the theory of behavioral economics may offer useful policies and strategies for improving food selections.